El universo fantasmagórico en la obra de Pekka Jylha - 1955 - Centella, Visitación Ortega (2019)
We enter in the universe of mythological fables of western popular culture, which has taken leadership the animal kingdom, either by the presence from the black cat, the goat or those that are related, for the overnight habitat or their black’s fur or feathers, to present through our article the work of Finnish artist Pekka Jylhä. The interest generated serving the phenomenological contents linked with darkness and his conception through contemporary art, which in turn, underlying ideas about the duality of the existential issues that man has been planted since the beginning of time